Carbon Dioxide Dry Reforming of Glycerol for Hydrogen Production using Ni/ZrO2 and Ni/CaO as Catalysts - Nur Nabillah Mohd Arif; Dai-Viet N. Vo; Mohammad Tazli Azizan; Sumaiya Zainal Abidin (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2016)
Glycerol, byproduct from the biodiesel production can be effectively utilized as the promising source of synthesis gas (syngas) through a dry reforming reaction. Combination of these waste materials with greenhouse gases which is carbon dioxide (CO2) will help to reduce environmental problem such as global warming. This dry reforming reaction has been carried out in a fixed bed batch reactor at 700 °C under the atmospheric pressure for 3 hours. In this experiment, reforming reaction was carried out using Nickel (Ni) as based catalyst and supported with zirconium (ZrO2) and calcium (CaO) oxides. The catalysts were prepared by wet impregnation method and characterized using Bruanaer-Emmett-Teller (BET) surface area, Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), Thermo Gravimetric (TGA), and Temperature Programmed Reduction (TPR) analysis. Reaction studies show that 15% Ni/CaO give the highest hydrogen yield and glycerol conversion that peaked at 24.59% and 30.32%, respectively. This result is verified by XRD analysis where this catalyst shows low crystallinity and fine dispersion of Ni species resulted in high specific surface area which gives 44.93 m2/g that is validated by BET.